(untitled) (Research, Society and Development, 2021)
The way in which both the School and the University are currently structured shows a model of education that has existed for over a century. However, this same model is unable to sustain the new challenges of contemporary society. This reinforces the need for the development and application of new teaching methodologies and methods, which favor a change from the dominant mental model to systemic thinking, autonomy, innovation and the solution of real problems that motivate learners for effective learning. The Lego® Serious Play® methodology fulfills these functions, but it needs to be understood and used. Based on this context, this study aims to understand how the Lego® Serious Play® methodology can contribute to the qualification of autonomy and, as a consequence, of the results in the learning process in active learning environments in higher education, since this methodology is totally innovative and disruptive, provides great gains in engagement and productivity of the learners involved, in addition to enhancing skills in creativity, communication, cooperation and solving complex problems. The present study takes a methodological perspective based on the action research method; in relation to the technical procedures used, the bibliographical research and the case study stand out; as for the method of approach, the hypothetical-deductive method was chosen. It is concluded that the Lego® Serious Play® methodology appears as an alternative to contribute to improving the results of the learning process in active learning environments in higher education. Such methodology encourages autonomy, systemic thinking and transdisciplinarity, in which the learner needs to know the ’whole’, developing a systemic, holistic and global view of the facts.